Development of a prototype fingerprint safety padlock using arduino for motorcycle / Muhammad Nur Eidham Norizan and Wan Muhammad Syahmi Wan Fauzi - Norizan, Muhammad Nur Eidham; Wan Fauzi, Wan Muhammad Syahmi (School of Mechanical Engineering, 2022)
As a mode of transportation, people nowadays prefer to use motorcycles rather than any other vehicles as it is easier to maneuver through a crowded area and better fuel consumption. Since motorcycles bring more advantages, especially in traffic problems, the number of motorcycles increases each year. However, there are also disadvantages due to the high number of motorcycles. One of the disadvantages is the rise of stolen motorcycle cases. To prevent the cases from increasing, padlocks are already invented and used to solve this common problem. The project for Final Year Project (FYP) is the adjustment and improvement of the product which is the existing padlock which is a fingerprint safety padlock using Arduino for motorcycles. The objective of this project is to design Arduino based fingerprint safety padlock for motorcycles using state-of-art SolidWorks 2017 and to fabricate the designed fingerprint safety padlock as a proof of concept. The methodology starts from the concept generation, followed by the design, and fabrication process of the product. The results of this project are that the product made has its own specifications, advantages, and disadvantages. The conclusion is the objectives are achieved since the product is successfully designed and fabricated.